2020
DOI: 10.1038/s41371-020-00433-z
|View full text |Cite
|
Sign up to set email alerts
|

The capacity of primary health care centers in Jordan to manage hypertension: areas for improvement

Abstract: The assessment of the capacity of Primary Health Care (PHC) settings for the management of hypertension is essential to identify areas for improving management outcomes. This study aimed to assess the capacity of PHC centers in Jordan to manage hypertension including the assessment of human resources, equipment, and infrastructure. All comprehensive PHC centers located in Irbid and Mafraq governorates in north of Jordan (n = 23) were assessed. An assessment tool from HEARTS Technical Package was adapted and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…In Jordan, the lack of updated national guidelines for the management of hypertension that provide up-todate information and facilitate the translation of new evidence into clinical practice contributes to the challenges in managing hypertension (11). Therefore, this study aimed to adapt, implement, and evaluate hypertension control following the implementation of the HEARTS Technical Package in six health centers in Jordan.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Jordan, the lack of updated national guidelines for the management of hypertension that provide up-todate information and facilitate the translation of new evidence into clinical practice contributes to the challenges in managing hypertension (11). Therefore, this study aimed to adapt, implement, and evaluate hypertension control following the implementation of the HEARTS Technical Package in six health centers in Jordan.…”
Section: Discussionmentioning
confidence: 99%
“…The low blood pressure control rate could also be explained by the Jordanian health system capacity and readiness for hypertension management. A recent assessment of 23 health centers in Jordan found poor availability of and training on evidence-based guidelines for hypertension in Jordan (11). Additionally, a recent unpublished study in Jordan showed that most NCDs management guidelines were outdated and did not re ect the best available evidence (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nurses are dealing with cases from different acuity levels, and all necessary resources (especially medications) are always available in most emergency departments. However, there is a lack of updated guidelines of emergency treatments and management ( Al-Hadeethi et al, 2022 ; Suleiman, Hijazi, Al Kalaldeh, & Sharour, 2019; Nusairat, 2006 ).…”
Section: Methodsmentioning
confidence: 99%